Rufinamide: crystal structure elucidation and solid state characterization - Salunke, Nita; Thipparaboina, Rajesh; Chavan, Rahul B.; Lodagekar, Anurag; Mittapalli, Sudhir; Nangia, Ashwini; Shastri, Nalini R. (Journal of Pharmaceutical and Biomedical Analysis, 2018)
Rufinamide (R) is a triazole derivative approved for the management of partial seizures and seizures associated with Lennox-Gastaut Syndrome, in November 2007. Crystal structure, solid state characterization, drug-excipient compatibility and solubility play a pivotal role in formulation development. This work deals with the crystal structure elucidation of R by single crystal X-ray diffraction and solid state characterization by thermal, spectroscopic and crystallographic techniques. Drug- excipient compatibility was assessed by differential scanning calorimetry (DSC). New RP-HPLC method for quantification of R was developed with improved retention time. Solubility and dissolution of drug in different media was determined. Additionally, the flow behavior of the drug was evaluated by measuring Carr's index and Hausner's ratio, while the compressibility behavior was studied using Well's protocol. R crystallized from dimethylformamide (R-DMF) was utilized for single crystal analysis. The drug crystallized in triclinic crystal system with P-1 space group. Asymmetric unit cell consists of two molecules of R held by intermolecular hydrogen bond (connected by N-H center dot center dot center dot O, which forms the catemeric chain). Analytical outcomes from DSC, thermogravimetric analysis (TGA) and powder X-ray diffraction (PXRD) revealed that the drug was present in pure crystalline form and was devoid of any polymorphic or pseudopolymorphic impurities. Influence of pH on the solubility and dissolution of R-DMF was found to be insignificant. The drug exhibited poor aqueous solubility, which was improved nearly 4.6 fold with the addition of 2% sodium lauryl sulphate (SLS). The drug exhibits poor flow and elastic compression nature. Excipients such as poly ethylene glycol (PEG) 8000, SLS, lactose monohydrate, starch and Hydroxypropyl methylcellulose (HPMC) E15 were incompatible with R-DMF as identified by thermal analysis. It is envisaged that these information regarding solid state properties of R-DMF would aid in identifying a logical path for formulation development. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Compressibility; Dissolution media; DSC; HPLC method; solubility

Role of hydrogen bonding in cocrystals and coamorphous solids: indapamide as a case study - Allu, Suryanarayana; Suresh, Kuthuru; Bolla, Geetha; Mannava, M. K. Chaitanya; Nangia, Ashwini (Crystengcomm, 2019)
The stronger sulfonamide-pyridine (SO2NH2 center dot center dot center dot N-Py) and sulfonamide-carboxamide (SO2NH2 center dot center dot center dot O = C-NH) hydrogen bonds direct the formation of cocrystals, while the weaker sulfonamide-amine (SO2NH2 center dot center dot center dot N-H) hydrogen bond results in coamorphous products. IDP-PIP and IDP-ARG coamorphous solids exhibit remarkable stability under accelerated conditions.

Resolving salt-cocrystal conundrum in multicomponent crystals by using X-ray quantum crystallography - Sudheendranath, Athul; Tothadi, Srinu; Pradhan, Amit Kumar; Prajapati, Aditya Kumar; Nangia, Ashwini; Thomas, Sajesh P. (Journal of Physical Chemistry C, 2025)
The structural identity of multicomponent crystals as a salt or cocrystal is dictated by the proton transfer state between the molecular components. In pharmaceutical drugs, solid-state forms such as salts or cocrystals can have significantly distinct stability, dissolution, and solubility profiles. The accurate location of proton positions is a formidable task using conventional X-ray crystallography, as the atomic scattering factors are based on spherical electron density models. Herein, we demonstrate that the X-ray quantum crystallographic (QCr) technique of Hirshfeld Atom Refinement (HAR), based on aspherical atomic scattering factors, can be effectively employed to resolve this riddle. Our HAR models accurately located the proton positions, thus distinguishing salts, cocrystals, and continuum crystal structures, which are substantiated by the N 1s binding energies from X-ray photoelectron spectroscopy (XPS) corresponding to the base components in a series of crystals. The QCr models reveal the subtle features of electron localization and bonding around the double-well potential in the intermolecular proton-transfer regions in these crystals.